2006
DOI: 10.1159/000090206
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Determinants of Calcification in Intracranial Arteries in Chinese Patients Who Underwent Computed Tomography Examinations

Abstract: Background: Intracranial artery calcification is common but the prevalence and determinants are not well established. We aim to describe the prevalence and location of calcification in intracranial arteries according to brain multi-detector-row computed tomography (MDCT) images, and to investigate its correlation with potential risk factors. Methods: We studied consecutive men and women referred for brain CT in December 2004. All patients received a questionnaire regarding their medical history related to athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 42 publications
10
78
2
Order By: Relevance
“…17 One study found an independent association between sex and intracranial internal carotid artery calcifications, 11 whereas another study did not find this association. 10 In the present study, we found that smoking and hypercho- lesterolemia are independently associated with the presence of intracranial calcifications. Other studies showed independent associations of smoking with coronary, aortic arch, carotid bifurcation calcifications 4,5,18,19 and intracranial internal carotid artery calcifications.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…17 One study found an independent association between sex and intracranial internal carotid artery calcifications, 11 whereas another study did not find this association. 10 In the present study, we found that smoking and hypercho- lesterolemia are independently associated with the presence of intracranial calcifications. Other studies showed independent associations of smoking with coronary, aortic arch, carotid bifurcation calcifications 4,5,18,19 and intracranial internal carotid artery calcifications.…”
Section: Discussionsupporting
confidence: 52%
“…Consequently, previous studies made use of a qualitative grading system. [8][9][10][11][12] Although Taoka et al 13 used commercially available software to assess the Agatston score of intracranial calcifications, they had to eliminate the contamination of bone attenuation on wide-windowed CT images. We developed custom-made software for quantification of intracranial calcifications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations